Jovenes Fotografos 1987. - Salaamadis, Madrid (Madrid : Instituto de la Juventud, 1987)
Sunico-Vacas, Cayetano ; Cervera Merlo, Juan Miguel ; Rojo Ramos, Angel ; Menendez Artime, Matias ; Garcia Saenz, Alberto ; Lopez Mateo, Antonio ; etc.
Jovenes Fotografos 1987, Salaamadis, Madrid, 30 junio / 29 agosto 1987
boek